Imago 2000 : Encuentros de Fotografia y Video. - Barbeito, Patricia Felisa; Beccaria, Marcella; Boris, Staci; Doherty, Claire; Fiedler, Andreas; Kaiser, Philipp; Larcade, Franck; Lowry, Joanna; Lozano, Amparo; Morrissey, Simon; Pfaff, Lilian; Consorcio Salamanca 2002; et al. (Salamanca : Universidad de Salamanca, 2000)
Balogh, Istvan ; Dean, Mark ; Dobai, Sarah ; Hubbard, Teresa ; Birchler, Alexander ; Lane, Abigail ; McMurdo, Wendy ; Mesa-Pelly, Deborah ; Montilla, Julia ; Paradeis, Florence ; Prego, Sergio ; Starkey, Hannah ; Stewart, Christopher
biog., ind. tent., gr. tent., bibliog. p. 91-112
Spaans
Imago 2000 : Encuentros de Fotografia y Video, Salamanca 2002, Junta de Castilla y León, Salamanca, 19.07 - 20.08.2000
boek